PENGAWASAN DINAS PERDAGANGAN, KOPERASI, USAHA KECIL DAN MENENGAH PROVINSI RIAU TERHADAP PEREDARAN BARANG PADA TOKO ELEKTRONIK DI KECAMATAN TENAYAN RAYA TAHUN 2017-2018 - Muhammad Iqbal; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Office of Trade, Cooperatives, Small and Medium Enterprises in Province of Riau is the government agencies with the controlling duties in the goods circulation in the entire the Province of Riau. Tenayan Raya District is the area with the largest number of electronic stores in Pekanbaru. A controller is needed to ensure the goods circulation is in accordance with the Indonesian National Standard (SNI), as well as to ensure the protection of the goods for the community. But in reality, many electronic shop owners in Tenayan Raya Subdistrict do not understand which items are permitted or prohibited for sale related to SNI. This is caused by the lack of controlling by the Department of Trade, Cooperatives, Small and Medium Enterprises in Riau. The formulation of the problem in this study is how do the Riau Province's Office of Trade, Cooperatives, Small and Medium Enterprises supervise the goods circulation at Electronic Stores in Tenayan Raya during 2017-2018 and what are the factors that affect the controlling.The purpose of this study is to determine the controlling of the Department of Trade, Cooperatives, Small and Medium Enterprises of Riau Province on the goods circulation at electronic stores in Tenayan Raya during 2017-2018 and the factors that affected the controlling. The theory concept that the researcher uses is the function of controlling according to Bohari. This study uses a qualitative approach with descriptive methods. In collecting data, the researcher uses interview techniques and documentation. The results of the research are the controlling of the Department of Trade, Cooperatives, Small and Medium Enterprises of Riau Province on the goods circulation in electronic stores in Tenayan Raya Subdistrict during 2017-2018 were not optimal. It is proven by the number of items which are not in accordance with SNI provisions. The factors that influence this controlling are the condition of Human Resources in the Department of Trade, Cooperatives, Small and Medium Enterprises in Riau. The second factor is the role of the leader, in this case the Head of the Department of Trade, Cooperatives, Small and Medium Enterprises in Riau. The next factor is the lack of community participation in providing information to the mentioned department.. Keywords: Controlling, circulation of electronic goods